2023
DOI: 10.3390/foods12010181
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Effect of Metabolites from a New Strain Lactiplantibacillus Plantarum LPP703 Isolated from Naturally Fermented Yak Yogurt

Abstract: The antifungal effect of metabolites produced by a new strain of Lactiplantibacillus (Lpb.) plantarum LPP703, isolated from naturally fermented yak yogurt, was investigated. The results showed that Lpb. plantarum LPP703 significantly inhibited four fungal species, including Penicillium sp., Rhizopus delemar, Aspergillus flavus, and Aspergillus niger. The metabolites produced after 20 h of Lpb. plantarum LPP703 fermentation showed the highest antifungal activity against Penicillium sp. Compared with the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…L. plantarum produces antifungal substances active against molds, including Aspergillus sp. [39,40]. Although the antifungal activity of lactic acid bacteria in Japanese post-fermented tea has not yet been investigated, it may contribute to the selection and control of fungi in post-fermented tea.…”
Section: Contribution Of Lactic Acid Bacteria To Bioactivitymentioning
confidence: 99%
“…L. plantarum produces antifungal substances active against molds, including Aspergillus sp. [39,40]. Although the antifungal activity of lactic acid bacteria in Japanese post-fermented tea has not yet been investigated, it may contribute to the selection and control of fungi in post-fermented tea.…”
Section: Contribution Of Lactic Acid Bacteria To Bioactivitymentioning
confidence: 99%
“…Yak milk contains a variety of microorganisms that are beneficial to human health [98]. Studies have found that beneficial bacteria isolated and identified from yak yogurt have multiple functional activities, such as antibacterial [63,99], blood glucose regulation [100], weight loss and lipid-lowering effects [101], and improving gastric ulcers [102]. However, currently, yak yogurt is limited to household production without fixed production standards and has a short shelf life, which makes large-scale production impossible [103,104].…”
Section: Yak Milk Productsmentioning
confidence: 99%